Kato Nan Ampek Dalam Tambo Alam Minangkabau Karya Ibrahim Dt. Sanggoeno Diradjo: Analisis Hermeneutika Wolf - Muharram, Syahrul; Burhanuddin, Nunu (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of the study is to find out the meaning of kato nan ampek in the Minangkabau tradition in the book